Tool and chemical probe development for emerging targets in Alzheimer's disease: The Emory‐Sage‐SGC TREAT‐AD Center. (31st December 2021) - Mangravite, Lara M; Betarbet, Ranjita; Carter, Gregory W; Frye, Stephen V.; Fu, Haian; Gileadi, Opher; Greenwood, Anna K; Leal, Karina; Longo, Frank M.; Omberg, Larsson; Pearce, Kenneth H.; Edwards, Aled M; et al.
Abstract: Background: Alzheimer's disease (AD) is the most common form of dementia, with no effective preventative strategies or treatments. The drug development pipeline in AD has been marked by repeated failures to find an effective treatment. Increasing evidence supports the need for greater pipeline target diversity and new approaches to target the disease. The Emory‐Sage‐SGC TREAT‐AD Center (https://treatad.org) was established to forge a new path forward with the aim of developing drugs for emerging targets in AD beyond the two pathological hallmarks. By casting a wider net, we aim to develop tools and chemical probes that target the multifaceted dysregulation in the brains of AD patients, and expand the portfolio of therapeutic approaches to break the cycle of failure. We believe that this more‐inclusive perspective will enrich the AD field and advance the discovery of potential drug targets for AD. Method: The Emory‐Sage‐SGC TREAT‐AD Center has selected a diverse set of novel AD targets derived from systems biology studies within the Accelerating Medicines Partnership in AD (AMP‐AD) consortium and further evaluated using data from multiple AD consortia and existing literature. Targets nominated through the AMP‐AD consortium were scored based on unbiased bioinformatic assessments across multiple lines of evidence including genetic, multi‐omic, neuropathological, and literature‐based metrics and were mapped to mechanistic hypotheses residing in distinct biological domains that are altered in AD. Target Enabling Packages, including expression constructs, knockout cell lines, assays, antibodies and crystal structures, are being generated for 20 proteins prioritized using this approach. Hit characterization and chemical probe development has started for targets in which the evidence for AD biology is strong. All data and reagents will be publicly shared through standard repositories and cataloged at the Agora site (https://agora.adknowledgeportal.org). Result: The Emory‐Sage‐SGC Center goals are: to identify and prioritize novel emerging targets for AD; to generate reagents and tools for emerging targets to encourage the community to expand the pipeline of potential AD therapeutic targets; and to share all data, tools, and reagents openly, rapidly, and without restriction. Conclusion: All data, protocols, reagent sets, and chemical tools and will be made widely available. For more information see www.treatad.org.